Smart Grids – Fundamentals and Technologies in Electricity Networks - Buchholz, Bernd M.; Styczynski, Zbigniew; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer Vieweg, 2014)
Efficient transmission and distribution of electricity is a fundamental requirement for sustainable development and prosperity. The world is facing great challenges regarding the reliable grid integration of renewable energy sources in the 21st century. The electric power systems of the future require fundamental innovations and enhancements to meet these challenges. The European Union’s “Smart Grid” vision provides a first overview of the appropriate deep-paradigm changes in the transmission, distribution and supply of electricity. The book brings together common themes beginning with Smart Grids and the characteristics of new power plants based on renewable energy and /or highly efficient generation principles. It covers the advanced technologies applied today in the transmission and distribution networks and innovative solutions for maintaining today’s high power quality under the challenging conditions of large-scale shares of volatile renewable energy sources in the annual energy balance. Besides considering the new primary and secondary technology solutions and control facilities for the transmission and distribution networks, prospective market conditions allowing network operators and the network users to gain benefits are also discussed. The growing role of information and communication technologies is investigated. The importance of new standards is underlined and the current international efforts in developing a consistent set of standards are described in detail. The presentation of international experiences to apply novel Smart Grid solutions to the practice of network operation concludes this book. The authors of the book worked for many years to develop Smart Grid solutions within national and international projects and to introduce them in the practice of network operations.
Vision and Strategy for the Electricity Networks of the Future -- Smart Generation – Resources and Potentials -- Modern Technologies and the Smart Grid Challenges in Transmission Networks -- Design of Distribution Networks and the Impact of New Network Users -- Smart Operation and Observability at the Transmission Level -- The 3 Pillars of Smart Distribution -- Design of the Smart Energy Market -- Advanced Information & Communication Technologies: The Backbone of Smart Grids -- Smart Grids Worldwide -- Abbreviations.
Keywords: Energy systems; Power electronics; Renewable energy resources; Energy Systems; Power Electronics, Electrical Machines and Networks; Renewable and Green Energy